Strategic investment strategy for software companies using a multi-criteria decision analysis approach - Rietveld, Mike; van Dijk, Jolijn; Gülüm Taş, Pelin (Journal of Supply Chain Management Science, 2023)
Strategic investments are crucial for software companies as they determine the direction and growth of the businesses. Parallel to continuous improvements in information technologies, increased customer expectations, and competitive environments, deciding between new investment strategies has become even more important. Despite their prevalence, making these decisions is generally challenging, especially when there are multiple alternatives, conflicting objectives, and a group of decision-makers with different priorities. In this study, we consider this complex issue as a multi-criteria decision-making problem by focusing on a real-life case study from a software company that specializes in selling tools for online education and assessment. We propose a two-level methodology integrating the Best-Worst method (BWM) and Elimination and Choice Translating Reality (ELECTRE-III). In the first step, six criteria that play a role in software investment decisions are defined based on an extensive literature review and expert interviews. Then a group of experts compared these criteria by using BWM, and importance weights were calculated. In the third step, the ELECTRE-III method is utilized to evaluate a set of investment alternatives and provide a ranking. We conclude with insights for both researchers and practitioners who are concerned about strategic investment decisions.